Working together: A review of cross-sector collaborative practices in provision for children with special educational needs and disabilities. (January 2022) - Castro-Kemp, Susana; Samuels, Alecia
Highlights: Cross-sector collaboration is essential for effective SEND provision and positive children's outcomes. Little systematic evidence is available on the specific strategies to be used to increase high quality collaborations. Multidisciplinary, interdisciplinary, and transdisciplinary traditions frame cross-sector collaborations in practice. There is a need for more evidence-based research on interdisciplinary and transdisciplinary cross-sector partnerships. Abstract: It is widely recognised that cross-sector partnerships are key to improve outcomes for children with special educational needs and disabilities (SEND). However, evidence-based strategies fostering these partnerships have not been systematically identified, and terms designating different forms of collaboration are used interchangeably. This study aims to contribute to systematically identify practices for cross-sector collaboration for children with SEND, critically positioning these within collaborative traditions ( multidisciplinarity, interdisciplinarity and transdisciplinarity ). A scoping review of the international literature of the past 10 years was conducted, following Arksey and O'Malley's methodology and considering type of SEND studied, country of origin, approach to collaboration portrayed and study design. Only papers describing empirical applications of collaborative strategies were included in the final review (n = 8). Practices identified ranged from multidisciplinary to transdisciplinary and included: partnerships between higher education and healthcare organisations, implementation of school clinics, schools as interdisciplinary hubs, management's own partnerships and networks, assessment in person with the whole team, videoconferencing, periodic meetings with key professionals, informal on-site discussions and transdisciplinary play-based assessment. Implications for practice are considered, in particular the need to examine how these strategies are implemented in a variety of settings and the need to develop the skills that elicit transdisciplinary work.